2014
DOI: 10.1097/01.aoa.0000452154.50151.0f
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Groups Practicing Participatory Learning and Action to Improve Maternal and Newborn Health in Low-Resource Settings

Abstract: Topic: Systems-based Practice M aternal and neonatal mortality rates remain high in many low-income and middle-income countries. To attain the Millennium Development Goals 4 and 5, different approaches to improve birth outcomes have been tried, including community-based interventions. Effects on survival have been heterogeneous and uncertain. This systematic review and meta-analysis of randomized controlled trials (RCTs) was done to assess the effects of women's groups practicing participatory learning and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…In seven of the studies, groups were trained using a common participatory learning and action (PLA) cycle; these are also the seven studies reviewed in Prost et al. (). Each group was encouraged to identify and implement its own combination of strategies, such as developing health education programmes, establishing vegetable gardens or purchasing bed nets to address health challenges (Colbourn et al., ; Prost et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In seven of the studies, groups were trained using a common participatory learning and action (PLA) cycle; these are also the seven studies reviewed in Prost et al. (). Each group was encouraged to identify and implement its own combination of strategies, such as developing health education programmes, establishing vegetable gardens or purchasing bed nets to address health challenges (Colbourn et al., ; Prost et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies of interventions that mobilized women's groups to promote maternal and newborn health find that such group‐based interventions are highly cost effective (Colbourn et al., ; Ensor et al., ; Lewycka et al., ; Manandhar et al., ; Prost et al., ; Roy et al., ; Tripathy et al., ), suggesting that provision through SHGs can provide economies of scale. Lewycka et al.…”
Section: Existing Theory and Evidence On Self‐help Groupsmentioning
confidence: 99%
“…Conducting educational groups for pregnant women is an important tool in reducing maternal and neonatal mortality among women living in rural areas, and should be considered in other contexts (27) . In Brazil, however, conducting groups with pregnant women is still an underused strategy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent MSPAS (2011) survey found that young women are more likely to talk about family planning with friends than with sisters, mothers or other family members. Moreover, a recent meta-analysis found that women's groups engaging in participatory learning led to improved maternal and neonatal health outcomes in resource-poor settings (Prost et al, 2013). The social support and informal learning fostered within social networks have led them to become a popular approach to current poverty reduction and women's empowerment initiatives in Guatemala (Cattell, 2001;Prost et al, 2013;UNFPA, 2010UNFPA, , 2013UNFPA, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent meta-analysis found that women's groups engaging in participatory learning led to improved maternal and neonatal health outcomes in resource-poor settings (Prost et al, 2013). The social support and informal learning fostered within social networks have led them to become a popular approach to current poverty reduction and women's empowerment initiatives in Guatemala (Cattell, 2001;Prost et al, 2013;UNFPA, 2010UNFPA, , 2013UNFPA, , 2014. Although programming geared towards empowering women and girls through wider education and economic opportunities is widely supported as a strategy for improving reproductive health and economic outcomes, little research is available that analyses this approach in great depth (Grépin and Klugman, 2013;Samandari and Speizer, 2010;Victora and Barros, 2013).…”
Section: Introductionmentioning
confidence: 99%